Community psychosocial practices carried out by victims of Colombian armed conflict. Literature Review - Sánchez Agudelo, Paula Vanessa (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
The article presents a literature review on community psychosocial practices undertaken by victims to face the damages within the framework of the Colombian armed conflict, documented since 2011. The literature review was conducted through the SCOPUS, CEPAL, DIALNET, JSTOR databases, where 110 documents were found, of which were analyzed using the coding process suggested by Grounded Theory. The results are presented into three major trends, as a result of selective coding. The first trend is the relational dimension that underlies all psychosocial action processes, the second is the identification of the most frequent and infrequent audiences of these processes and the consequences thereof, and the third is a constant interrogation of the institutional role in psychosocial action processes. These results are critically reflected upon in the discussion, highlighting the importance of collective coping, and suggesting a narrative perspective as an approach to address the identified issues.